One-year study evaluating efficacy of an iodine-restricted diet for the treatment of moderate-to-severe hyperthyroidism in cats - Loftus JP (Dove Medical Press, 2019)
John P Loftus, Sage DeRosa, Angela M Struble, John F Randolph, Joseph J Wakshlag Department of Clinical Sciences, College of Veterinary Medicine, Cornell University, Ithaca, NY 14853, USA Purpose: This study sought to determine the efficacy of a therapeutic iodine-restricted diet during a 12 -month interval in cats with moderately to severely increased total thyroxine (TT4) concentrations. Patients and methods: Eight hyperthyroid cats with serum creatinine 6.0 µg/dL (reference interval 1.5–4.0 µg/dL) were enrolled. Each cat underwent an initial physical examination, complete blood count, serum chemistry panel, thyroid profile, thyroid scintigraphy, and echocardiogram. Physical examination and all blood samplings were repeated at 1, 2, 3, 6, and 12 months after enrollment. Clients were instructed to feed only the therapeutic iodine-restricted diet throughout the entire study. Results: Median TT4 was 8.4 (range 6.2–24.0) µg/dL at study onset. Thyroid scintigraphy was abnormal in all cats, confirming hyperthyroidism. Six out of eight cats had normal serum TT4 after 4 weeks of feeding the therapeutic diet. The two cats that did not achieve normalization of TT4 at 4 weeks had the highest initial TT4 concentrations. Three cats were withdrawn from the study due to emergence of chronic kidney disease. Conclusion: An iodine-restricted diet was able to control moderate-to-severe hyperthyroidism in most (six out of eight) of the cats by 4 weeks. Cats with highest baseline TT4 took substantially longer before TT4 concentrations normalized, if at all. Keywords: feline, thyroxine, free T4, nuclear scintigraphy, iodine